Gender and preferences for non-farm income diversification: A framed field experiment in Ghana - Kramer, Berber; Lambrecht, Isabel B. (International Food Policy Research Institute, 2019)
Many rural development programs aim at improving women’s economic empowerment in agriculture, but as rural income continues to diversify, women may prefer investing in nonfarm activities. In a framed field experiment with 1,527 men and women in Ghana, we elicit preferences for investments in crop farming versus other business activities. We analyze whether gender differences in preferences for non-farm diversification, if any, can be ascribed to differential access to physical and human capital, and to what extent a gender gap is explained by differences in socio-economic characteristics, skills, perceptions and norms. Despite strong beliefs that men and women are more skilled in crop farming and non-farm businesses, respectively, many respondents invest in both farm and non-farm activities and we find only a small gender gap in revealed preferences for non-farm diversification. This gap can be largely explained by gender stereotyping around perceived skills. Increasing access to physical and human capital does not significantly affect preferences. We conclude that both men and women reveal a strong preference for diversified investments, which needs to be reflected in programs and policies aiming to improve women’s economic empowerment.